Reliability and validity of the Meaningfulness of Songwriting Scale with university students taking a popular songwriting class. Issue 1 (2nd January 2018) - Baker, Felicity Anne; MacDonald, Raymond Afredo Rossi; Pollard, Mark Clement
Abstract: Background : Songwriting is emerging as a popular activity for use in therapeutic contexts suggested. Our study tested the properties of the Meaningfulness of Songwriting Scale (MSS) with university students studying songwriting, to determine its validity and reliability in measuring the extent of meaning derived from the songwriting process.Method : Participants completed the MSS, Short State Flow Scale, and Rosenberg Self-Esteem Scale immediately following their creation and performance of an original song. Seven days later, participants completed the MSS second time.Results: Analyses were performed and findings indicated that the measure has good content validity, strong internal consistency, acceptable test–retest reliability, limits of agreement, measurement error, and discriminant validity. Convergent validity was weaker than the other measurement property results.Conclusions: The MMS has adequate measurement properties for use with university students and may be utilized to further our understanding of the process and outcomes of this emerging, and potentially highly beneficial, music therapy strategy. Future research should seek to further investigate the psychometric properties of these instruments across different populations and contexts.